2002
DOI: 10.1046/j.1365-2923.2002.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing prescribing: an intern's perspective

Abstract: At a critical time in skills development, interns encounter many forces that can potentially impact on prescribing practices in both positive and negative ways. Our data contribute to the understanding of the multifaceted learning environment of interns and may be useful in providing a foundation for prescriber education programmes tailored to the specific needs of junior doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 20 publications
4
61
0
Order By: Relevance
“…It is also implied in the literature that junior doctors or medical students might seek out advice of a senior nurse in relation to certain procedures, or medication advice. Pearson et al 12 examined factors which influence intern prescribing. The results from the qualitative study confirmed registrars as being the most approachable for advice; however, they did acknowledge nurses’ experience and guidance in prescribing medications.…”
Section: Discussionmentioning
confidence: 99%
“…It is also implied in the literature that junior doctors or medical students might seek out advice of a senior nurse in relation to certain procedures, or medication advice. Pearson et al 12 examined factors which influence intern prescribing. The results from the qualitative study confirmed registrars as being the most approachable for advice; however, they did acknowledge nurses’ experience and guidance in prescribing medications.…”
Section: Discussionmentioning
confidence: 99%
“…10 Sampling continued until theme redundancy. 16 A preliminary interview topic guide was developed with input from the steering committee.…”
Section: Methodsmentioning
confidence: 99%
“…This tension between 'experience and evidence' and managing the complexities of relating within a hierarchical medical culture are a common experience for the doctor in training. [18][19][20] Similarly, qualitative studies of hospital trainees report that prescribing is influenced by the habits of senior supervising clinicians, who are the 'opinion leaders' as to how and when to deviate from guidelines. 21 Less experienced doctors may prescribe more appropriately according to guidelines, 22 but develop behaviours 23 and prescribing habits similar to their supervisors as training progresses.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%